Swift logic for big data and knowledge graphs - Bellomarini, L; Gottlob, G; Pieris, A; Sallinger, E (Association for the Advancement of Artificial Intelligence, 2017)
Many modern companies wish to maintain knowledge in the form of a corporate knowledge graph and to use and manage this knowledge via a knowledge graph management system (KGMS). We formulate various requirements for a fully-fledged KGMS. In particular, such a system must be capable of performing complex reasoning tasks but, at the same time, achieve efficient and scalable reasoning over Big Data with an acceptable computational complexity. Moreover, a KGMS needs interfaces to corporate databases, the web, and machinelearning and analytics packages. We present KRR formalisms and a system achieving these goals.